RTKs activate the ERK 1/2 MAPK cascade - Cobb, Melanie H. (Henry Stewart Talks, 2007)
Regulation of the MAPK pathway by receptor tyrosine kinases through Ras, MAPK cascade paradigm, Regulatory properties of kinase cascade components, MAPK structure, Generating specificity in MAPK cascades, Docking mechanisms, MAPK scaffolds, Feedback mechanisms and pathway interactions, Regulation of the localization of ERK1/2, Functional versatility of MAPK pathways